2016
DOI: 10.1016/j.ijscr.2016.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral hearing loss and facial palsy in an operated case of vestibular schwannoma—Case report

Abstract: HighlightsRare complication of contralateral hearing loss and facial palsy following vestibular schwannoma surger.The exact cause is uncertain and various theories are proposed to ascertain the cause.Treatment options are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The degree of hearing impairment in the contralateral ear varied from mild to profound SNHL; including mild, 22 , 25 , 30 moderate, 3 , 20 , 22 , 25 , 26 moderate to severe, 3 , 22 , 25 severe, 3 , 4 , 8 , 20 , 24 , 26 - 28 and profound 6 , 7 , 21 , 25 , 29 degree of hearing loss. It has been suggested that hearing thresholds before vestibular schwannoma surgery could be regarded as an important factor to predict CoHL outcomes following tumor removal.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of hearing impairment in the contralateral ear varied from mild to profound SNHL; including mild, 22 , 25 , 30 moderate, 3 , 20 , 22 , 25 , 26 moderate to severe, 3 , 22 , 25 severe, 3 , 4 , 8 , 20 , 24 , 26 - 28 and profound 6 , 7 , 21 , 25 , 29 degree of hearing loss. It has been suggested that hearing thresholds before vestibular schwannoma surgery could be regarded as an important factor to predict CoHL outcomes following tumor removal.…”
Section: Discussionmentioning
confidence: 99%
“…In our electronic database, there were multiple pure-tone audiogram measurements per patient. Since, as mentioned earlier, subclinical and pronounced contralateral hearing loss after surgery was detected in several patients, [17][18][19][20][21][22][23][24][25][26][27][28] the last measurement directly before therapy and the most recent puretone audiogram after therapy were used for the comparison. For patients under the wait-and-scan strategy, the most recent puretone audiogram was used for analysis.…”
Section: Pure-tone Audiometrymentioning
confidence: 99%
“…There are case reports documenting contralateral hearing loss after surgical removal of VSs. 17-26 Furthermore, Walsted et al 27,28 demonstrated in 2 prospective studies that more than half of their patients had a small threshold increase after VS surgery, which might be subclinical. Probably the most accurate explanation for this phenomenon is intraoperative loss of CSF, which leads to decreased pressure of CSF and, via the cochlear aqueduct, also of the perilymph.…”
mentioning
confidence: 99%
“…Sanna modified the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) grading scheme to reflect more accurately what kind of hearing is being preserved, and reported that class A or B was obtained in 6.8% of the middle cranial fossa approach patients and in 16.7% of the retrosigmoid approach patients, while the figures were 32.2% and 31.3%, respectively, when the AAO-HNS system was applied ( Sanna et al., 2004 ). Even contralateral hearing loss and facial paralysis have been associated with excessive loss of cerebrospinal fluid ( Lustig et al., 1995 , Shuto et al., 2011 , Warade et al., 2016 ). New tinnitus also appeared postoperatively in 39.8% of VS patients ( Levo et al., 2000c ).…”
Section: The Risks and Complications Of Active Treatmentsmentioning
confidence: 99%